A molecular phylogeny of Cochylina, with confirmation of its relationship to Euliina (Lepidoptera: Tortricidae). (26th August 2019) - Brown, John W.; Aarvik, Leif; Heikkilä, Maria; Brown, Richard; Mutanen, Marko
Abstract: This work presents a multiple‐gene phylogenetic analysis of 70 species representing 24 genera of Cochylina and eight species representing eight genera of Euliina, and a maximum‐likelihood analysis based on 293 barcodes representing over 220 species of Cochylina. The results confirm the hypothesis that Cochylina is a monophyletic group embedded within a paraphyletic Euliina. Six major monophyletic lineages are recognized and defined within Cochylina: a Phtheochroa Group, a Henricus Group, an Aethes Group, a Saphenista Group, a Phalonidia Group and a Cochylis Group. The work summarizes the groups (including related genera not included in our analysis), provides morphological characters that support the molecular data, and compares results to previous phylogenies of Cochylina. The following nomenclatural changes are proposed: Brevicornutia, rev.stat. ; Neocochylis, rev.stat. ; Paracochylis, rev.stat. ; Pontoturania, rev.stat. ; and Platphalonidia, rev.stat. Abstract : The previously proposed hypothesis that Cochylina is a monophyletic group embedded within a paraphyletic Euliina is confirmed. Six major monophyletic lineages within Cochylina are recognized and defined: a Phtheochroa Group, a Henricus Group, an Aethes Group, a Saphenista Group, a Phalonidia Group and a Cochylis Group. The elevation of several subgenera of Cochylis to generic status vastly improves monophyly within the Cochylis Group.